The Effect of Fair Treatment, Cooperative Attitude, and Anticipatory Socialization on the Intention to Conduct Whistleblowing in Local Government (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study aims to determine the effect of fair treatment, cooperativeness, and anticipatory socialization on whistleblowing intentions among civil servants in the local government environment. Design/Methodology/Approach: The sample included 166 civil servants from several Local Government Units (LGUs) within the East Kutai Regency Regional Government. Data were collected using a questionnaire. This study used the purposive sampling method and data analysis utilizing SPSS 15.0. Research findings: The results revealed that cooperativeness positively affects the intention to whistleblowing, while fair treatment and anticipatory socialization have no impact on the intention to whistleblowing. Theoretical contribution/Originality: The Theory of Planned Behavior emphasizes the importance of a cooperative social environment in increasing the employees' intention to report violations. Developing a supportive work culture is more important than simply implementing a formal policy to encourage whistleblowing behavior. Practitioner/Policy implication: There is a need for teamwork training, open communication, and a whistleblowing policy that protects and rewards.